Effect of Temperature Variation PWHT Dissimilar Welding Low Carbon Steel ASTM A36 with ASTM A240 Type 316L - Wahab, Abd.; Arma, Lukmanul Hakim; Arsyad, Hairul; Othman, Rozaini Bin (EPI International Journal of Engineering, 2024)
Abstract ASTM A36 low carbon steel is steel commonly used in construction, and the austenitic stainless steel 316L series is stainless steel with good corrosion resistance. Joining two dissimilar metals is unavoidable because it can provide good mechanical properties and resist corrosion at a low cost. This study studied the effect of variations in post-welding heating process temperature (PWHT) on mechanical properties and microstructure by shield metal arc welding (SMAW) low carbon steel ASTM A36 with ASTM A240 type 316L with a thickness of 6 mm with a single V connection and using an E308L-electrode. 16. The PWHT process was carried out to improve the weld results with variations in heating temperatures of 400, 600, and 900˚C with a holding time of 1 hour with 15% dromos quenching media. Testing mechanical properties includes hardness test using micro Vickers method on low carbon steel base metal, HAZ, weld metal, HAZ, and stainless steel base metal and impact test using Charpy method. Optical microscopes were used to study the microstructure of the area of the base metal, HAZ, and weld metal viewed using a laser scanning microscope. The test results show that the highest average hardness value in the weld metal area is in the specimen without PWHT with a value of 124.96 HV and samples with a PWHT temperature of 400˚C on the weld metal 121.63 HV and the lowest in the PWHT specimen 900˚C 76.17 HV. in the HAZ 316L area. The hardness value of the weld metal without PWHT and PWHT indicates that the hardness value is higher than the two-parent metals. While the impact test with PWHT specimens at 400˚C had higher impact energy than specimens without PWHT by 6.50 %, and the lowest was 16.26% at the optimum temperature of 900˚C, the shape of the samples showed ductile cracks.